Effect of polyploidy on phosphoglucose isomerase diversity in Festuca microstachys. - Adams, W T (1977)
Studies of the inheritance of electrophoretic banding patterns in Festuca microstachys support the hypothesis that three closely related loci, one located in each of the three ancestral genomes, code the multiple phosphoglucose isomerase (glucosephosphate isomerase; D-glucose-6-phosphate ketol-isomerase, EC 5.3.1.9) variants found in this hexaploid species. The close relationship among the three loci is indicated by the observation that hybrid enzymes of intercistronic origin form when the loci in different genomes carry alleles coding homodimers with unlike migration rates. Homozygous individuals fixed for different alleles in different genomes produce hybrid enzymes and, when self-fertilized, they breed true for isozyme patterns normally found only in the heterozygotes of diploid species. Biochemical diversity due to this "fixed heterozygosity" is high in F. microstachys; although this species is more than 99% self-fertilized the proportion of individuals with at least one heterodimer exceeded 61% in all of the 16 natural populations studied and it exceeded 92% in 11 of the populations. This great biochemical diversity may contribute to the ability of F. microstachys to survive in the wide range of habitats in which it is found over western North America.